The role of endoplasmic reticulum stress in hippocampal insulin resistance - Sims-Robinson, Catrina (Exp Neurol, 2016)
Metabolic syndrome, which includes hypertension, hyperglycemia, obesity, insulin resistance, and dyslipidemia, has a negative impact on cognitive health. Endoplasmic reticulum (ER) stress is activated during metabolic syndrome, however it is not known which factor associated with metabolic syndrome contributes to this stress. ER stress has been reported to play a role in the development of insulin resistance in peripheral tissues. The role of ER stress in the development of insulin resistance in hippocampal neurons is not known. In the current study, we investigated ER stress in the hippocampus of 3 different mouse models of metabolic syndrome: the C57BL6 mouse on a high fat (HF) diet; apolipoprotein E, leptin, and apolipoprotein B-48 deficient (ApoE 3KO) mice; and the low density lipoprotein receptor, leptin, and apolipoprotein B-48 deficient (LDLR 3KO) mice. We demonstrate that ER stress is activated in the hippocampus of HF mice, and for the first time, in ApoE 3KO mice, but not LDLR 3KO mice. The HF and ApoE 3KO mice are hyperglycemic; however, the LDLR 3KO mice have normal glycemia. This suggests that hyperglycemia may play a role in the activation of ER stress in the hippocampus. Similarly, we also demonstrate that impaired insulin signaling is only present in the HF and ApoE 3KO mice, which suggests that ER stress may play a role in insulin resistance in the hippocampus. To confirm this we pharmacologically induced ER stress with thapsigargin in human hippocampal neurons. We demonstrate for the first time that thapsigargin leads to ER stress and impaired insulin signaling in human hippocampal neurons. Our results may provide a potential mechanism that links metabolic syndrome and cognitive health.